2018
DOI: 10.2147/dddt.s171286
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Ginsenoside Rg1 and Astragaloside IV reduces oxidative stress and inhibits TGF-β1/Smads signaling cascade on renal fibrosis in rats with diabetic nephropathy

Abstract: IntroductionAnti-oxidative stress and inhibition of TGF-β1/Smads signaling cascade are essential therapeutic strategies for diabetic nephropathy (DN). In this study, we aimed to explore the effect of combination of Ginsenoside Rg1 and Astragaloside IV on oxidative stress and TGF-β1/Smads signaling in DN rats.Materials and methodsWistar rats were divided into five groups: N group, M group (streptozotocin [STZ], intraperitoneally), G group (STZ rats with Ginsenoside Rg1, intragastrically [ig]), A group (STZ rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 39 publications
3
44
0
Order By: Relevance
“…In addition, studies show that ginsenoside Rg1 can alleviate liver fibrosis, chronic obstructive pulmonary disease, and [20][21][22]. Previous studies show that ginsenoside Rg1 combined with astragaloside IV can protect renal function, which may be related to antioxidant stress and inhibition of TGF-β1/Smads pathway [23]. In this study, we confirmed the protective effect of ginsenoside Rg1 on renal function in diabetic nephropathy rats and further examined the effects of ginsenoside Rg1 on autophagic activity and podocyte EMT.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, studies show that ginsenoside Rg1 can alleviate liver fibrosis, chronic obstructive pulmonary disease, and [20][21][22]. Previous studies show that ginsenoside Rg1 combined with astragaloside IV can protect renal function, which may be related to antioxidant stress and inhibition of TGF-β1/Smads pathway [23]. In this study, we confirmed the protective effect of ginsenoside Rg1 on renal function in diabetic nephropathy rats and further examined the effects of ginsenoside Rg1 on autophagic activity and podocyte EMT.…”
Section: Discussionsupporting
confidence: 76%
“…A. Mey and Astragaloside IV from Radix astragali have also improved fibrosis and inflammation in STZ-induced diabetic nephropathy by inhibiting TGF-β/Smad2/3 while enhancing Smad7 signaling (Du et al, 2018). Asperulosidic acid, a bioactive iridoid glycoside, can also exert renal protective effects by inactivating both TGF-β/Smad and NF-κB signaling pathways (Xianyuan et al, 2019).…”
Section: Treatment Of Ckd By Targeting Downstream Tgf-β/smad Signalinmentioning
confidence: 99%
“…Furthermore, the inhibitory effects of Rg1 on the activation of NLRP3 were reversed by LEU, which strongly suggested that Rg1 decreased hyperlipidemia-induced pyroptosis in podocytes by inhibiting the mTOR/NF- κ B/NLRP3 axis. A previous study showed that the combination of Rg1 and astragaloside relieved renal fibrosis in DN by inhibiting the TGF- β 1/Smads pathway and oxidative stress [ 33 ]. Consistent with this, Rg1 significantly reduced proteinuria, improved renal function, and alleviated tissue damage in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks after STZ injection, the successfully modelled DN rats were randomly divided into the (untreated) DN and ginsenoside Rg1-treated groups ( n = 8 in each group) and administered with vehicle (aqua distillate) or 50 mg/kg ginsenoside Rg1 once daily by oral gavage for 8 weeks. This dose of ginsenoside Rg1 has been proved to be effective and safe [ 33 ]. At the end of the regimen, the rats were anaesthetized adequately; then, the urine creatinine (UCr), urinary microalbumin (Malb), blood urea nitrogen (BUN), and serum creatinine (Scr) levels were measured.…”
Section: Methodsmentioning
confidence: 99%